2021
DOI: 10.1016/j.envpol.2021.116621
|View full text |Cite
|
Sign up to set email alerts
|

Compromising situation of India’s bio-medical waste incineration units during pandemic outbreak of COVID-19: Associated environmental-health impacts and mitigation measures

Abstract: COVID-19 induced pandemic situations have put the bio-medical waste (BMW) management system, of the world, to test. Sudden influx, of COVID-infected patients, in health-care facilities, has increased the generation of yellow category BMW (Y-BMW) and put substantial burden on the BMW-incineration units of India. This study presents the compromising situation of the BMW-incineration units of India, in the wake of COVID-19 pandemic, from 21 st March, 2020 to 31 st Aug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 44 publications
1
70
1
Order By: Relevance
“…The possibility of confirmed COVID-19 cases and deaths has been increasing due to the continuous changing of the genome sequence of the coronavirus and its community transmission. Due to this pandemic, biomedical wastes (BMW) concerns not only to physicians or nurses, but to other HCPs such as pharmacists, technicians, interns, and therapists in hospitals and all healthcare sectors [ 5 , 6 ] as there was a paradigm shift in the form of the huge amount of wastes generated. There was an unexpected increase in the amount of disposable personal protective equipment (PPE), such as gloves, surgical mask, N-95 masks, air-purifying respirators, goggles, face shield, safety gowns or suits and shoe covers, as well as the use of plastic syringes and needles, high-flow nasal cannulas, and breathing circuits [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of confirmed COVID-19 cases and deaths has been increasing due to the continuous changing of the genome sequence of the coronavirus and its community transmission. Due to this pandemic, biomedical wastes (BMW) concerns not only to physicians or nurses, but to other HCPs such as pharmacists, technicians, interns, and therapists in hospitals and all healthcare sectors [ 5 , 6 ] as there was a paradigm shift in the form of the huge amount of wastes generated. There was an unexpected increase in the amount of disposable personal protective equipment (PPE), such as gloves, surgical mask, N-95 masks, air-purifying respirators, goggles, face shield, safety gowns or suits and shoe covers, as well as the use of plastic syringes and needles, high-flow nasal cannulas, and breathing circuits [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…0 Analysis revealed that on an average, each COVID-19 infected patient in India generates approximately 3.41 kg/d of BMW and average proportion of yellow BMW (which is highly infectious) in it is 50.44%. 3 Massive amounts of medical waste have already been generated and disposed of into the natural environment 4 and waste mismanagement practices can increase the contamination risks in developing countries. 5 At this time of crisis, with limited resources and manpower available, these are difficult to store and transport.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is recommended to use available alternative technologies for the production of biomedical equipment and treatment of COVID-19-related waste. 65,66 Moreover, disposable PPE becomes one of the major factors in environmental pollution and source of biohazards creating critical environmental issues globally. If this remains unsolved, it may be a long-term threat to human and aquatic organisms.…”
Section: Protective Efficiency Safety and Durationmentioning
confidence: 99%
“…It puts a substantial burden and results in a health compromising situation including carcinogenic health impacts questioning for other alternative technologies for the production of biomedical equipments and treatment of COVID-19 related wastes. 65,66 Moreover, single-use PPE types become factors in environmental pollution and sources of biohazards. Not only the discarded PPEs, but also their derived decomposition products are threatening the aquatic organisms and human life that may persist for many years in the future.…”
Section: Nanotechnology For Improvement Of Personal Protection Equipment (Ppe)mentioning
confidence: 99%